2007
DOI: 10.1209/0295-5075/80/27001
|View full text |Cite
|
Sign up to set email alerts
|

Tunable magnetocaloric effect in RTi 1−x Mo x Ge (R = Tb, Er) (x = 0, 0.15) compounds

Abstract: The tetragonal layered compounds TbTiGe and ErTiGe order antiferromagnetically at 276 K and 39 K, respectively. Partial substitution of Mo for Ti in these two compounds modifies the magnetic interactions giving rise to a ferromagnetic ground state which results in an enhanced magnetocaloric effect. The magnetic entropy change in ErTi0.85Mo0.15Ge for a magnetic field change of 5 T is ∼ 10.5 J/kg/K as against ∼ 0.8 J/kg/K for ErTiGe in the vicinity of the magnetic transition. Thus, magnetocaloric properties of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
(10 reference statements)
1
10
0
Order By: Relevance
“…The CeFeSitype forms present magnetocaloric properties associated to a field-induced magnetic phase transition [11]. Concerning the magnetocaloric effect of the CeScSi-type forms only few studies are reported, for instance ErTi 0.85 Mo 0.15 Ge exhibits MCE around 62 K [12]. In this paper, we report on the synthesis of GdScSi and GdScGe and their investigation using X-ray powder and single crystal diffraction and magnetization measurements.…”
Section: Introductionmentioning
confidence: 95%
“…The CeFeSitype forms present magnetocaloric properties associated to a field-induced magnetic phase transition [11]. Concerning the magnetocaloric effect of the CeScSi-type forms only few studies are reported, for instance ErTi 0.85 Mo 0.15 Ge exhibits MCE around 62 K [12]. In this paper, we report on the synthesis of GdScSi and GdScGe and their investigation using X-ray powder and single crystal diffraction and magnetization measurements.…”
Section: Introductionmentioning
confidence: 95%
“…A similar result was also observed in ErTiGe compound. 18,19 The anomaly at low temperature ͑T AF = ϳ 9 K͒ may be associated with a possible change from collinear to noncollinear AFM structure. 19 The transition at a higher temperature corresponds to a change from AFM to paramagnetic ͑PM͒ state with increasing temperature, and its Néel temperature T N is determined to be 46 K. It is also found from Fig.…”
Section: Methodsmentioning
confidence: 99%
“…18,19 The anomaly at low temperature ͑T AF = ϳ 9 K͒ may be associated with a possible change from collinear to noncollinear AFM structure. 19 The transition at a higher temperature corresponds to a change from AFM to paramagnetic ͑PM͒ state with increasing temperature, and its Néel temperature T N is determined to be 46 K. It is also found from Fig. 2 that the magnetic susceptibility of the ErTiSi compound at temperatures above ϳ65 K perfectly follows the Curie-Weiss law m −1 = ͑T − p ͒ / C m , where p is the PM Curie temperature and C m is the Curie-Weiss constant.…”
Section: Methodsmentioning
confidence: 99%
“…The large changes in magnetization values around the critical field reflect in the temperature dependence of S m and T ad . For example, the Dy 5 Si 2 Ge 2 , DySi and RTiGe compounds show interesting metamagnetic behaviour in their magnetically ordered state [39][40][41]. In particular, the Dy 5 Si 2 Ge 2 compound (orthorhombic, Sm 5 Ge 4 -type) orders antiferromagnetically with T N ∼ 56 K and undergoes metamagnetic transition at temperatures below 40 K. This leads to enhanced magnetocaloric effect with an additional peak feature below T N for field changes above 2 T ( figure 3).…”
Section: Materials Showing Metamagnetic Transitionmentioning
confidence: 99%